GENOME-WIDE ASSOCIATION STUDY OF ENDURANCE GENES IN PROFESSIONAL WRESTLERS (Experimental biology, 2026)
The study aimed to identify genetic factors associated with endurance in professional wrestlers from the Republic of Kazakhstan using a genome-wide association study (GWAS). The dataset included 58 elite combat-sport athletes and 60 non-athletic controls. Genotyping was conducted on the iScan platform (Illumina) with the Infinium Global Screening Array-24. Quality control procedures in PLINK v1.9 and subsequent analyses in R (qqman) retained 296,772 SNPs after filtering for call rate, Hardy–Weinberg equilibrium, minor allele frequency, and exclusion of sex-chromosomal and mitochondrial variants. Principal component analysis showed no substantial population stratification, and the genomic inflation factor (λ = 1.02) indicated minimal confounding. At the suggestive significance level (p < 1×10⁻⁵), several loci showed differences between athletes and controls, including rs12916133, rs7765401, GSA-rs1682809, and rs4777639. These variants are located near PPEF2, SV2B, CDC37L1, and the non-coding region LOC105370982, which are genes and regulatory elements involved in calcium-dependent signaling, synaptic regulation, proteostasis, and muscular adaptation. Although none reached genome-wide significance (p < 5×10⁻⁸), the detected trends point to a contribution of regulatory and neurometabolic pathways to endurance-related traits in wrestlers.The study is limited by the moderate sample size and the need for replication in independent Kazakhstani and international cohorts. Nevertheless, the findings form a basis for personalized training strategies and future integrative multi-omics research in sports genomics.
Keywords: GWAS, single nucleotide polymorphism (SNP), endurance, sports genetics, wrestlers, genetic polymorphism